Relationship between serum growth differentiation factor 15, fibroblast growth factor-23 and risk of atrial fibrillation: A systematic review and meta-analysis - Tan, Ziqi; Song, Tiangang; Huang, Shanshan; Liu, Menglu; Ma, Jianyong; Zhang, Jing; Yu, Peng; Liu, Xiao (Frontiers in Cardiovascular Medicine, 2022)
Background and Objective: Growth differentiation factor-15 (GDF-15) and fibroblast growth factor-23 (FGF-23) are considered predictors of the incidence of cardiovascular diseases. The present meta-analysis aimed to elucidate the associations between GDF-15 and FGF-23 in the risk of atrial fibrillation (AF). Methods: An electronic search was conducted in the Cochrane Library, PubMed, and Embase databases from inception until February 27, 2021. The study protocol was registered in the PROSPERO database (CRD42020182226). Results: In total, 15 studies that enrolled 36,017 participants were included. Both serum FGF-23 and GDF-15 were elevated in patients with AF. Analysis of categorical variables showed higher serum FGF-23 levels were associated with an increased risk of AF (relative risk (RR)=1.28, 95% confidence interval (CI): 1.05-1.56). In contrast, this association was not found with GDF-15 (RR=0.91, 95% CI: 0.20-4.04). In dose-response analysis, a linear positive association was noted between serum FGF-23 levels and the risk of AF (P nonlinear = 0.9507), with a RR elevation of 7% for every 20 pg/ml increase in the serum FGF-23 levels (95% CI: 1.02-1.13). No remarkable relationship was found between serum GDF-15 levels and the risk of AF, and the overall RR for the association between a 100 ng/L increment in GDF-15 levels and AF was 1.01 (95% CI: 0.998-1.02). Conclusion: Our study showed a positive linear correlation between serum FGF-23 levels and the risk of AF. However, no significant association was found between GDF-15 and the risk of AF. Further studies are warranted to clarify whether serum FGF-23 levels may be considered in predicting the risk of AF.